Risk and Protective Factors of Indonesian Women Migrant Workers in Malaysia - Artaria, Myrtati Dyah; Herdiana, Ike; Alaydrus, Sayf Muhammad; Suen, Mein-Woei (Jurnal Ilmiah Peuradeun, 2025)
This study was conducted to identify the risk and protective factors of Indonesian women migrant workers in Malaysia. The risk factors are variables that contribute to one’s psychological stresses, while the protective factors are variables that contribute to one’s mental stability. The “risk and protective” concept is fluid, relative, and often overlaps according to the individuals and situations. Data for the qualitative study was gathered using semi-structured interviews with five Indonesian women migrant workers in Malaysia. The risk factors include family poverty, poor communication, employee conflicts, and workplace hostility. Expertise and professional experience, as well as family and state support, are identified as protective factors. A combination of both protective and risk factors was also discovered, namely the recruitment and departure processes, educational background, work knowledge, working hours, healthcare access, and coping mechanisms. Understanding these aspects allows individuals to take precautions against problems upon arrival in their destination states. An insight provided by this study might inspire the stakeholders to increase international migrant workers’ protection framework and further ensure their human rights.